2023
DOI: 10.1029/2022gl101155
|View full text |Cite
|
Sign up to set email alerts
|

Superstoichiometric Alloying of H and Close‐Packed Fe‐Ni Metal Under High Pressures: Implications for Hydrogen Storage in Planetary Core

Abstract: The Earth's core is primarily composed of Fe alloyed with ∼5.5 wt.% Ni (McDonough, 2003). The observed density deficit suggests a considerable amount of light elements in the core (Birch, 1964). Hydrogen has been considered as one of the light element candidates (Poirier, 1994). Despite its dominance in planetary systems, however, the effects of hydrogen are not well understood because of experimental challenges associated with its study at high pressure-temperature (P-T). Thanks to recent technical advances, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
(112 reference statements)
3
4
0
Order By: Relevance
“…S3 and S4 A ). As shown in previous high-pressure studies, hydrogen alloys with liquid Fe metal at high - and form FeH , , which is also confirmed here ( 21 , 25 , 26 ) (in our experiments, ; SI Appendix , Fig. S5 ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…S3 and S4 A ). As shown in previous high-pressure studies, hydrogen alloys with liquid Fe metal at high - and form FeH , , which is also confirmed here ( 21 , 25 , 26 ) (in our experiments, ; SI Appendix , Fig. S5 ).…”
Section: Resultssupporting
confidence: 92%
“…At 8-13 GPa after heating, XRD patterns showed the peaks from Mg 2 FeH 6 , Mg(OH) 2 , face-centered cubic (fcc) FeH x , and MgO (Figs 2a, S3, and S4a). As shown in previous high-pressure studies, hydrogen alloys with liquid Fe metal at high P -T and form FeH x , Fe + 0.5xH 2 → FeH x , which is also confirmed here (21,25,26) (in our experiments, x = 1.0−1.2; Fig. S5).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations